Advances in biotechnology. proceedings of the Fifth International Yeast Symposium held in London, Canada, July 20-25, 1980 - Stewart, Graham G.; Russell, Ingre; Moo-Young, Murray (Advances in Biotechnology ;, 1981)
Advances in Biotechnology, Volume IV: Current Developments in Yeast Research covers the proceedings of the Fifth International Yeast Symposium. The book presents several papers that discuss several aspects of yeast. Comprised of 95 chapters and organized into eight sections, the book first discusses the industrial and agricultural uses of yeast, and then covers genetics. The third section reviews sporulation and conjugation. Section IV tackles biochemistry, while Section V and Section VI talk about taxonomy, ecology, and cell cycle. The seventh section covers the Phaff symposium and the last s.